Block and Boost DNA Transfer: Opposite Roles of OmpA in Natural and Artificial Transformation of Escherichia coli - Sun, Dongchang; Wang, Bing; Zhu, Lihong; Chen, Mengyao; Zhan, Linlin (PLOS ONE, 2013)
Our previous work established that DNA is naturally transferable on agar plates through a new transformation system which is regulated by the stationary phase master regulator RpoS in Escherichia coli. In this transformation system, neither additional Ca2+ nor heat shock is required. Instead, transformation is stimulated by agar. The membrane protein OmpA, a gated pore permeable to ions and larger solutes, serves as a receptor for DNA transfer during bacteriophage infection and conjugation. However, it remains unknown how DNA transfers across membranes and whether OmpA is involved in transformation of E. coli. Here, we explored potential roles of OmpA in natural and chemical transformation of E. coli. We observed that ompA inactivation significantly improved natural transformation on agar plates, indicating that OmpA blocks DNA transfer. Transformation promotion by ompA inactivation also occurred on soft plates, indicating that OmpA blocks DNA transfer independent of agar. By contrast, compared with the wild-type strain, chemical transformation of the ompA mutant was lower, indicating that OmpA has a role in DNA transfer. Inactivation of ompA also reduced chemical transformation in solution containing less Ca2+ or with a shortened time for heat shock, suggesting that the promotion effect of OmpA on DNA transfer does not solely rely on Ca2+ or heat shock. We conclude that OmpA plays opposite roles in natural and chemical transformation: it blocks DNA uptake on agar plates but promotes DNA transfer in the liquid Ca2+ solution. Considering that no single factor was identified to reverse the function of OmpA, we propose that multiple factors may cooperate in the functional reversal of OmpA during natural and artificial transformation of E. coli. Finally, we observed that ompA transcription was not affected by the expression of RpoS, excluding the possibility that RpoS regulates DNA transfer by suppressing ompA transcription.